Introduction - Hassan, S.M. (Springer, 2020)
Wireless sensor networks (WSNs) have gained wide acceptance in the industry especially with the recent approval of three industrial wireless network standards WIA-PA, WirelessHART and ISA100 wireless. Â© 2020, Springer Nature Switzerland AG.